Insights into the design of inhibitors of the EGFR family with anticancer activity overcoming resistance: a case of optimizing thieno[2,3-d]pyrimidine-based EGFR inhibitors - Milik, Sandra; Abdel-Aziz, Amal Kamal; El-Hendawy, Morad M.; El-Gogary, Riham I.; Saadeldin, Mona Kamal; Minucci, Saverio; Klein, Christian D.; Abouzid, Khaled A. M. (Journal of molecular structure, 2022)
EGFR inhibitors have been in clinical use for the treatment of non-small cell lung cancer and breast cancer for years. However, generation after generation of the developed EGFR inhibitors have been met by clinical resistance. In an attempt to develop the next generation of EGFR inhibitors, compound (2) was selected as a lead for optimization. (2) was identified during a previous study for the development of thieno[2,3-d]pyrimidine-based dual EGFR/HER2 inhibitors where it demonstrated good dual EGFR/HER2 inhibition and selective anti-proliferative activity against the lapatinib-sensitive cancer cell lines. Additionally, it showed modest activity against the T790M/L858R EGFR mutant. Twelve derivatives based on (2) were designed with the aim of optimizing the enzymatic and cellular activity of (2). Those twelve derivatives were prepared and tested for their inhibitory activities against EGFR, HER2 and T790M/L858R, and for their anti-proliferative activity against the cancer cell lines A431 and MDA-MB-468, and the NCI-60 panel of human cancer cell lines. The results provide an insight into the structural features required for EGFR/HER2 inhibition, and the conclusions drawn from this study could help direct future development of EGFR inhibitors that can overcome the current resistance mechanisms.